The Narration Method Of “Story Speech” In The Novel “Mawsim Al-Hijraila Al-Shamal”(Seasons Of Migration To The North) By Tayeb Salih - Bavanpouri, Masoud; Mottaqi, Amir Moqaddam; Ghaibi, Abdolahad; Motavali, Hadiseh (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
The speech of characters is one of the important elements of story as it defines the thoughts of the story and it can promote the events of story. A narrator transfers the speech from the author to the reader and it is manifested as “The narration methods of story speeches”. The story speeches are dived into five groups as direct, indirect, free direct and free indirect and narrative report. In the famous novel “Mawsim al-Hijraila alShamal” by “Tayeb Salih”, contemporary Sudani author, the mentioned methods are manifested based on narrative situation of story. The story is started with the first-person view and the narrator presents the report and other methods are dominant as the characters are increased. The present study is a descriptive-analytic design showing that the direct speech is highly frequent in the novel.